Growing into an unworldly gentleman: education, learning, isolation, and society in Maria Edgeworth’s Ormond - Haataja, Aino (My University, 2016)
This thesis studies the phenomena of education, learning, and societal constraint in Maria Edgeworth’s Ormond (1817). The eighteenth and nineteenth centuries saw the emergence of the educational theories of Rousseau, Locke, and of Edgeworth and her father, all of them influential in Europe. These theories and general developments in English and Irish educational systems are outlined in the early chapters of this thesis and form a theoretical backbone for it, along with ideals of masculinity in eighteenth and nineteenth-century England. Previous criticism of Ormond has produced political readings and more comprehensive overviews of the protagonist Harry’s learning process, and his stay in France. This study aims to provide so far lacking criticism that studies the opposition between the individual in their natural state in isolation and the constrained individual in society as exemplified in the contrasts between Cornelius and Sir Ulick O’Shane. My goal is to find out how Ormond would solve this contradiction, and what the novel is saying about society in general. My reading indicates that the text supports the preservation of the individual’s natural temper and feelings though restraining natural impulses that would be immoral or diminish the wellbeing of fellow-citizens when fully realized. Harry Ormond proceeds from isolation to elaborate society, enjoying both. However, as a result of romantic twists of plot and following his love, Harry eventually decides for retirement. The most important thing Harry learns by experience, which is his primary mode of learning, is self-control. Self-control and sincerity, that Harry owns, were part of the contemporary English masculine ideal, and thus Harry grows into an ideal English man.